Digital Watermarking Techniques and Trends - Nematollahi, Mohammad Ali.; Vorakulpipat, Chalee; Rosales, Hamurabi Gamboa; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book presents the state-of-the-arts application of digital watermarking in audio, speech, image, video, 3D mesh graph, text, software, natural language, ontology, network stream, relational database, XML, and hardware IPs. It also presents new and recent algorithms in digital watermarking for copyright protection and discusses future trends in the field. Today, the illegal manipulation of genuine digital objects and products represents a considerable problem in the digital world. Offering an effective solution, digital watermarking can be applied to protect intellectual property, as well as fingerprinting, enhance the security and proof-of-authentication through unsecured channels.
Preliminary on Watermarking Technology -- Audio Watermarking -- Speech Watermarking -- Image Watermarking -- Video Watermarking -- Three Dimensional (3D) Watermarking.
Keywords: Signal processing; Cryptography; Data encryption (Computer science).; Data protection; Information technology -- Management; Signal, Speech and Image Processing; Cryptology; Data and Information Security; Computer Application in Administrative Data Processing